2020
DOI: 10.1111/gcb.14997
|View full text |Cite
|
Sign up to set email alerts
|

Changing estuaries and impacts on juvenile salmon: A systematic review

Abstract: Estuaries are productive ecosystems providing important habitat for a diversity of species, yet they also experience intense levels of anthropogenic development. To inform decision‐making, it is essential to understand the pathways of impacts of particular human activities, especially those that affect species such as salmon, which have high ecological, social‐cultural and economic values. Salmon systems provide an opportunity to build from the substantial body of research on responses to estuary developments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Balanced against these positive signs is the drumbeat of warning signs: disappearing kelp beds (Berry et al, 2021), seagrass meadows threatened by disease (Groner et al, 2021), endangered resident orca whales (Wasser et al, 2017), changed flow in the Fraser River (Shrestha et al, 2012), habitat loss in its delta (Kehoe et al, 2020) and in the deltas of many other important rivers and streams (Brophy et al, 2019), and declining salmon runs (Figure 3; Losee et al, 2019;Pearsall et al, 2021), which exhibit lower marine survival in stocks from within the urban sea than from those outside. Salmon are an iconic species within this ecosystem and have been integral to Indigenous community identities for thousands of years; their decline is an important indicator of ecosystem change and one that integrates stressors across the urban estuarine landscape (Hodgson et al, 2020) and serves as an opportunity for innovative and time-tested management solutions (Atlas et al, 2021).…”
Section: Salish Sea As Urban Seamentioning
confidence: 99%
“…Balanced against these positive signs is the drumbeat of warning signs: disappearing kelp beds (Berry et al, 2021), seagrass meadows threatened by disease (Groner et al, 2021), endangered resident orca whales (Wasser et al, 2017), changed flow in the Fraser River (Shrestha et al, 2012), habitat loss in its delta (Kehoe et al, 2020) and in the deltas of many other important rivers and streams (Brophy et al, 2019), and declining salmon runs (Figure 3; Losee et al, 2019;Pearsall et al, 2021), which exhibit lower marine survival in stocks from within the urban sea than from those outside. Salmon are an iconic species within this ecosystem and have been integral to Indigenous community identities for thousands of years; their decline is an important indicator of ecosystem change and one that integrates stressors across the urban estuarine landscape (Hodgson et al, 2020) and serves as an opportunity for innovative and time-tested management solutions (Atlas et al, 2021).…”
Section: Salish Sea As Urban Seamentioning
confidence: 99%
“…), for example, move through many different ecosystems, jurisdictions, and political boundaries over the course of their lives. As stocks continue to decline over much of their range, many are pointing to the CE of a multitude of stressors as the culprits of this decline, though management actions continue to be narrow in scale in most jurisdictions (Price et al 2008;Lacy et al 2016;Hodgson et al 2020). Like spatial scale, the specified temporal scale can also greatly influence the conclusions of a CEA, but notably, Korpinen and Anderson (2016) found that no published CEA contains acknowledgment of or includes historical modifications to the environment.…”
Section: Defining Scalementioning
confidence: 99%
“…2016 ; Hodgson et al. 2020 ). Like spatial scale, the specified temporal scale can also greatly influence the conclusions of a CEA, but notably, Korpinen and Anderson ( 2016 ) found that no published CEA contains acknowledgment of or includes historical modifications to the environment.…”
Section: Shared Challengesmentioning
confidence: 99%
“…Streams and rivers are essential corridors for water, species, sediment, human activities, and other constituents of coastal watersheds. In heavily urbanized and agricultural watersheds, stormwater runoff (rain and melted snow) accumulates pollutants, such as bacteria, toxics, and excess nutrients, as it flows over landscapes en route to receiving waters, causing cascading impacts across the freshwater-estuarine gradient (Kennish, 2002;Hodgson et al, 2020). The quantity and toxicity of stormwater runoff is exacerbated by impervious surfaces and land conversion, and stormwater is the fastest growing cause of water quality degradation in coastal systems (Walsh et al, 2005;McCarthy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%